Non-Crossing Shortest Paths in Undirected Unweighted Planar Graphs in Linear Time - Balzotti, Lorenzo; Franciosa, Paolo (Journal of Graph Algorithms and Applications, 2022)
Given a set of terminal pairs on the external face of an undirected unweighted planar graph, we give a linear-time algorithm for computing the union of non-crossing shortest paths joining each terminal pair, if such paths exist. This allows us to compute distances between each terminal pair, within the same time bound. We also give a novel concept of incremental shortest path subgraph of a planar graph, i.e., a partition of the planar embedding in subregions that preserve distances, that can be of interest itself.